Carbon sequestration potential of different forest types in Pakistan and its role in regulating services for public health - Ali, Shahab; Khan, Shujaul Mulk; Ahmad, Zeeshan; Siddiq, Zafar; Ullah, Abd; Yoo, Sunghoon; Han, Heesup; Raposo, António (Frontiers in Public Health, 2023)
The higher amount of CO2 causes numerous health effects including headache, restlessness, difficulty in breathing, increase heart rate, blood pressure, asphyxia, dizziness, etc. This issue of increasing atmospheric CO2 can only be solved via above-ground and below-ground carbon sequestration (CS). This study was designed to determine the relationship between CS with CA, DBH, H, SR, and elevation in different forest types of Pakistan with the specific objective: (1) to quantify the direct and indirect relationship of Carbon sequestration with CA, DBH, H, and SR in various natural forest types, (2) to evaluate the effect of elevation on the trees functional traits and resultant CS. We used the linear Structural Equation Model (SEM) for each conceptual model. Our results confirmed that the highest CS potential was recorded for Dry Temperate Conifer Forests (DTCF) i.e., 52.67 %, followed by Moist Temperate Mix Forests (MTMF) and Sub-Tropical Broad-Leaved Forests (STBLF). The SEM further described the Carbon sequestration variation i.e., 57%, 32%, 19%, and 16% under the influence of CA (β = 0.90 and P-value < 0.0000), H (β = 0.13 and p-value = 0.009), DBH (β = 0.07 and p-value = 0.005), and SR (β = -0.55 and p-value = 0.000), respectively. The individual direct effect of SR on Carbon sequestration had been negative and significant. At the same time, the separate effect of CA, DBH, and H had positive and significant on Carbon sequestration. The remaining 20% of CS variations are indirectly influenced by elevation. It means that elevation affect Carbon sequestration indirectly through CA, DBH, H, and SR i.e. β = 0.133 and P-value < 0.166, followed by (β = 0.531 and P-value < 0.000, (β = 0.007 and P-value < 0.399), β = -0.32 and P-value < 0.000 ) respectively. It is concluded that CS has been mainly affected by elevation along with other biotic factors. Quantifying the role of various forest types in Carbon Dioxide (CO2) reduction and hence, improving the air quality is one of the imperative and novel studies via linking the dynamics of the biosphere and atmosphere.